Hubungan Pengetahuan, Sikap, Dan Dukungan Suami Dengan Pemberian Asi Eksklusif Di Wilayah Puskesmas Gambirsari Kota Surakarta - Muninggar, Intan; Kasjono, Heru S; Wijayanti, Anisa C (2016)
The Correlation of Knowledge, Attitude, and Husband Support with Exclusive Breastfeeding in Puskesmas Gambirsari Surakarta The exclusive breastfeeding program is a promotion program to feed baby with only breast milk without any other food and drink for 6 months. Exclusive breastfeeding program coverage is still under target 80% in national level, Jawa Tengah Province or in Surakarta. One factor that influence breasfeeding is husband support. This sudy aims to know the most influential variable toward exclusive breastfeeding in Puskesmas Gambirsari Surakarta. The method of this research is observation analytic using case control design. There were 94 samples that considered as 47 as cases and 47 as control. They were taken using cluster random sampling technique. Chi-Square used as bivariate analysis and Logistic Regression used as multivariate analysis. The results of bivariate analysis show that there are correlation between husband knowledge (p=0,0001), husband attitude (p=0,022), and husband support (p=0,039) with exclusive breastfeeding. Multivariate result shows that only husband knowledge that influencing exclusive breasfeeding (p=0,002; OR=4,055; 95%CI=1,636-9,987). That means possibility of non exclusive breasfeeding in husband with low knowledge was greater 4,055 times than husband with high knowledge.